A new method for obtaining the inconsistent elements in a decision table based on dominance principle - Ucan, Yasemen; Topal, Ahmet; Guler Bayazit, Nilgun (Tubitak Scientific & Technological Research Council Turkey, 2020)
In this study, using only the dominance relation, we propose a set defining inconsistent elements in the decision table. Then, we show the accuracy of our proposition with an example. We also express the computational complexity comparisons of the proposed method with general method in terms of the number of set intersection operations and the real number comparison operations.
Keywords: Rough sets; dominance relation; inconsistent element; decision table; Mathematics